Ranking the knowledge level of dental students using generalized TOPSIS method / Nurul Ain Syamimi Shamsudin and Nurul Khairunnisa Ramli - Shamsudin, Nurul Ain Syamimi; Ramli, Nurul Khairunnisa (2022)
The process of selecting the best alternative among the available options is known as decision making. Because of the imprecise or fuzziness of the linguistic terms, conventional crisp techniques have not been very effective in solving Multi-Criteria Decision Making (MCDM) problems. In the real world, finding exact values for MCDM problems is difficult or impossible. As a result, it is wiser to represent the alternative values as Single-Valued Neutrosophic Sets (SVNS) when applying the criteria. The truth-membership, indeterminacy-membership, and falsity-membership degrees of the neutrosophic set are more capable of catching up incomplete information. Thus, the technique for order preference by similarity to ideal solution (TOPSIS) method is extended to the MCDM problems with single-valued neutrosophic information in this paper. This research paper can tell researchers how to rank students’ level of understanding in diagnosing and treating patients effectively. Researchers and readers will be able to determine which student is the most capable in coping with emergency situations as a result of this. Furthermore, TOPSIS technique is a basic computation procedure that can be easily transcribed into a spreadsheet using the provided formula, this project is simple to comprehend. In this paper, the dental students’ level knowledge are identified and ranked using the value of relative closeness coefficient and have done comparative analysis since different method have been used. TOPSIS approach used in this paper gives consistent findings with existing data from previous research.